Agomelatine for postpartum depression and breastfeeding - Le Xiao (SAGE Publishing, 2021)
Postpartum depression (PPD) is a common and serious mental health problem that is associated with maternal suffering and numerous negative consequences for offspring. The benefit of breastfeeding for the infant and mother is well documented; therefore, the information about the risk-benefit of antidepressants, if used while mothers are breastfeeding, is necessary for the clinician's decision. The case series and systematic data on antidepressants in breastfeeding consist mainly of selective serotonin reuptake inhibitors (SSRIs), serotonin-norepinephrine reuptake inhibitors (SNRIs), and mirtazapine, whereas information on newer antidepressants such as agomelatine in pregnant or lactating women is rare, especially the adverse effects on the infant of the mother with PPD treated with agomelatine. To add to the limited available data, we report the case of agomelatine treatment in a breastfeeding woman with PPD. In this case report, we took advantage of the short half-life of agomelatine to reduce the potential effect on infant in the treatment of a nursing woman with PPD. The results confirm the effectiveness of agomelatine in the treatment of PPD and demonstrate the safety in breastfeeding.